Habitat Characteristics of the Honey Bee (Apis dorsata), Harvesting Methods of Forest Honey, and Characteristics of Sumbawa Forest Honey in Sumbawa Regency, Indonesia - Nila Wijayanti; Ade Mariyam Oklima; Siti Nurwahidah; Heri Kusnayadi (Journal of Global Sustainable Agriculture, 2022)
Sumbawa forest honey is honey produced by Apis dorsata bees. The problem faced is that Apis dorsata bees cannot be cultivated in stup and can only live in tall trees in the forest. This study aimed to determine the characteristics of Apis dorsata bees and Sumbawa forest honey. This research was conducted using a survey method, conducting field observations, interviews with several parties, and documentation. The research was conducted in Sumbawa Regency. The results of the study found that the survival of the Apis dorsata bee was highly dependent on forest sustainability. The taste and color of Sumbawa forest honey depend on the type of food or nectar consumed by Apis dorsata bees. This study concludes that Apis dorsata honey bees cannot be cultivated in stups, because this type of bee can only survive and thrive on tall trees in the forest. Sustainable harvesting techniques are carried out to sustain forest life and Apis dorsata bees. The price of Sumbawa forest honey varies based on its packaging, purity, water content, and distance traveled to collect it.